Young Men’s Experiences of Receiving Compassion from Others: A Narrative Exploration - Van Vliet, K. Jessica; Murdoch, Kenneth C.; Budzan, Brittany N. (Canadian Journal of Counselling and Psychotherapy, 2018)
The ability to receive compassion is essential for well-being and foundational to successful psychotherapy. Therapists must understand and attend to the unique ways in which men receive compassion when counselling males. However, research on this important topic has been limited. This qualitative study explored the meaning and experience of receiving compassion from the perspectives of young adult males. Utilizing narrative research methods, 10 themes were derived from 44 participants’ written compassion narratives. Suggestions for how counsellors may strengthen their compassionate exchanges with male clients and help them access compassion in their personal lives are discussed.